m6A RNA Methylation Regulators Act as Potential Prognostic Biomarkers in Lung Adenocarcinoma - Wang, Hongbo; Zhao, Xiangxuan; Lu, Zaiming (Frontiers in Genetics, 2021)
N6-methyladenosine [m(6)A/m6A] methylation is one of the most common RNA modifications in eukaryotic cell mRNA and plays an important regulatory role in mRNA metabolism, splicing, translocation, stability and translation. Previous studies have demonstrated that the m6A modification is highly associated with tumor cell proliferation, migration and invasion. In the present study, we have revealed that five m6A regulatory factors, namely Heterogeneous Nuclear Ribonucleoprotein A2/B1(HNRNPA2B1), Heterogeneous nuclear ribonucleoprotein C (HNRNPC), Vir like m6A methyltransferase associated (KIAA1429/VIRMA), RNA binding motif protein 15 (RBM15) and Methyltransferase like 3 (METTL3), which are closely related to the overall survival (OS) of patients with lung cancer. These five m6A regulatory factors exhibited potential prognostic value for the 1, 3 and 5-years survival outcomes of lung cancer patients. Our findings revealed that several signaling pathways, such as Cell cycle, DNA replication, RNA degradation, RNA polymerase, Nucleotide excision repair and basal transcription factors, are activated in the high-risk group of lung cancer patients.